412 T helper cell 17 is inversely related to clinical outcome to neoadjuvant chemotherapy in ovarian cancer. (13th November 2020) - Lou, G; Xia, B; Xie, H; Zhang, Y; Zhang, J; Fang, L; Mao, B; Zhang, H
Abstract : Background and Objective: Immune-related factors have the potential as prognostic biomarkers for treatments of cancers. Current study was to evaluate the correlation between the immune-related factors and the outcome of neoadjuvant chemotherapy (NAC) in patients with advanced ovarian cancer (OC) and select patients who would benefit from this strategy. Material and Methods: Prospective collection of serum samples from patients with OC who are treated with NAC at the Harbin Medical University Cancer Hospital between April 2017 and April 2018. Patients were divided into early-recurrence (ER) and late-recurrence (LR) groups according to whether relapsed within 2 years after surgery. Multiplexed magnetic beads immunoassays were performed on pre- and post-NAC serum samples to examine expression levels of 59 immune-related factors. Results: A total of 18 women were included, 8 in the ER group and 10 in the LR group. CA-125, IL-1beta, IL-2, IL4, IL-5, IL-17A, IL-23 and IL-27 decreased after NAC, whereas concentrations of IL-18, MCP-1, MIP-1alpha, MIP-1beta increased after NAC. Furthermore, the ER group had markedly higher T helper cell 17 (Th17) signature (average level of IL17A, IL21 and IL22) than LR group at both the pre- and post-NAC serum. Subsequent ROC curves analyses indicated a significant value of Th17 signature for predicting LR with an AUC of 0.813 (pre-NAC, p = 0.026) and 0.833 (post-NAC, p = 0.039), respectively. Conclusions: Our data showed NAC changed the expression of cytokines in the peripheral blood and elevated Th17 signature was associated with poor prognosis in OC patients with NAC.